2021
DOI: 10.1037/ser0000343
|View full text |Cite
|
Sign up to set email alerts
|

To what extent is psychological resilience protective or ameliorative: Exploring the effects of deployment on the mental health of combat medics.

Abstract: Exposure to a major traumatic stressor increases the odds of negative mental health and maladaptive behavioral outcomes not only for victims but also for 1st responders and health care professionals who are exposed to the aftermath. This study investigates the extent to which psychological resilience acts as either a Protective (i.e., vaccine-like) or an Ameliorative (i.e., antibiotic-like) factor to reduce the deleterious mental health outcomes associated with exposure to a major stressor. To do so, this pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Furthermore, it has been shown a positive relationship exists between psychological resilience and mental health [29]. For example, in a study analyzing whether psychological resilience is a protective or curative factor in adverse mental states that result from experiencing major stress [30], it was shown that psychological resilience is both protective and curative. Moreover, the intermediary role of resilience in perceived stress, anxiety and depression was highlighted [3].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown a positive relationship exists between psychological resilience and mental health [29]. For example, in a study analyzing whether psychological resilience is a protective or curative factor in adverse mental states that result from experiencing major stress [30], it was shown that psychological resilience is both protective and curative. Moreover, the intermediary role of resilience in perceived stress, anxiety and depression was highlighted [3].…”
Section: Discussionmentioning
confidence: 99%
“…Fear of negative evaluation is dispositional apprehension experienced during evaluative situations ( Rodebaugh et al, 2004 ; Weeks et al, 2005 ; Russell et al, 2021 ). The Brief Fear of Negative Evaluation Scale–Straightforward items (BFNE-S; Rodebaugh et al, 2004 ; Weeks et al, 2005 ) is an 8-item self-report measure used to assess fears of negative evaluation with the straightforward items from the original Brief Fear of Negative Evaluation Scale ( Leary, 1983 ; Carleton et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, resilience correlates negatively with mental health challenges ( Smith et al, 2008 ; Rodríguez-Rey et al, 2016 ; Sánchez et al, 2021 ). Among PSP, higher levels of self-reported resilience are associated with lower levels of symptoms related to PTSD and other mental health disorders (e.g., Smith et al, 2008 ; Lee et al, 2014 ; Kyriazos et al, 2018 ; Russell et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that those anxieties are symptomatic of PTSD, GAD, or depression, the accompanied stress may lead to higher levels of self-reporting these symptoms (i.e., victim mode). On the other hand, psychological resilience research finds that exposure to stress can serve both ameliorative and protective functions (Peterson, Chen, & Karver, 2019; Russell, Russell, Chen, Cacioppo, & Cacioppo, 2019). Similarly, there is a growing body of evidence of posttraumatic growth whereby some individuals exposed to a trauma find a positive benefit from the experience; for instance, they develop a greater sense of personal strength or a renewed appreciation for life (Janoff-Bulman, 2014; Tedeschi, Shakespeare-Finch, Taku, & Calhoun, 2018).…”
Section: Research Questionsmentioning
confidence: 99%